The impact of short-term adventure-based outdoor programs on college students' stress reduction. Issue 1 (2nd January 2019) - Chang, Yun; Davidson, Curt; Conklin, Seann; Ewert, Alan
ABSTRACT: This study examines the effect of short-term adventure-based outdoor programs (AOP) on reducing college students' stress levels. The effects of sex and different outdoor adventure activities in stress reduction are also evaluated. Thirty-three college students participated in selected short-term backpacking, canoeing, and kayaking programs. Student's salivary samples were collected to evaluate physiological stress response (as measured by levels of cortisol) and their psychological stress levels were collected through a modified 12-item questionnaire. Stress responses were measured at three different time points, including the second weekly meeting in the classroom, before the field trip, and at the conclusion of the field trip. Findings suggest that short-term AOP affords opportunities for college students to be away from daily challenges, and in turn reduce college students' psychological stress levels and provide a temporary relief of physiological stress levels. No significant differences in college students' stress levels were found between sex and different outdoor adventure activities.